KAJIAN YURIDIS TERHADAP EFEKTIVITAS PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) DAN KEPAILITAN SEBAGAI UPAYA PENAGIHAN UTANG DI INDONESIA - Habibie Abdiawan; Hery Chariansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the legal effectiveness of applications for Suspension of Debt Payment Obligations and bankruptcy as mechanisms for collecting debts in Indonesia. The research applies a normative juridical method using statutory, conceptual, and case approaches. Primary legal materials consist of the Indonesian Civil Code, Law Number 37 of 2004, Law Number 4 of 2023, Constitutional Court decisions, Supreme Court circulars, and commercial court decisions. The analysis shows that both procedures create collective enforcement and prevent fragmented executions, but their effectiveness differs. Suspension of Debt Payment Obligations is more suitable when a debtor still has a viable business and creditors need a binding restructuring plan. Bankruptcy is more appropriate when business rescue is no longer realistic and liquidation is required. Their practical effectiveness is reduced by the absence of a substantive insolvency test, strategic petitions, unequal bargaining power, limited disclosure, lengthy asset realization, and low recovery for concurrent creditors. The study proposes a proportional gatekeeping mechanism, stronger good faith examination, transparent creditor voting, independent valuation, and measurable supervision of administrators and receivers.